2014
DOI: 10.4172/2161-1017.1000144
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin in Liver Diseases

Abstract: Chemerin is a chemoattractant protein and moreover has a role in adipogenesis, angiogenesis and glucose homeostasis. Chemerin is primarily synthesized and secreted by adipocytes and hepatocytes. Chemerin receptors chemokine-like receptor 1 (CMKLR1), G-protein coupled receptor 1 (GPR1) and CC-motif chemokine receptorlike 2 (CCRL2) are all expressed in the liver suggesting that chemerin may be relevant in liver physiology and pathophysiology. Non-alcoholic fatty liver disease (NAFLD) is associated with obesity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Chemerin is abundant in adipocytes and hepatocytes and circulating chemerin levels were increased in obese patients (37). Previous studies have reported that circulating chemerin was not changed in HCC serum whereas its levels were induced in CRC patients (19,56,57). Our recent study showed comparable chemerin levels in the HCC and CRC patients with liver metastases (30).…”
Section: Discussionsupporting
confidence: 48%
“…Chemerin is abundant in adipocytes and hepatocytes and circulating chemerin levels were increased in obese patients (37). Previous studies have reported that circulating chemerin was not changed in HCC serum whereas its levels were induced in CRC patients (19,56,57). Our recent study showed comparable chemerin levels in the HCC and CRC patients with liver metastases (30).…”
Section: Discussionsupporting
confidence: 48%
“…2 SD = standard deviation. 3 Self-reported measures. Eleven data points missing/unknown/declined to state for the self-reported duration of diabetes, and four data points missing/unknown/declined to state for the smoking status.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Chemerin, also known as retinoic acid receptor responder protein 2 (RARRES2) or TIG2, is an adipokine and immunomodulator encoded by the RARRES2 gene [1][2][3][4][5][6]. This adipokine is synthesized as an inactive precursor that undergoes activation and a subsequent inactivation through a series of proteolytic cleavages [7,8].…”
Section: Introductionmentioning
confidence: 99%